Determination of the Activity of Bioactive Compounds from Biancaea sappan (L.) Tod. and Spatholobus ferrugineus (Zoll. and Moritzi) Benth Against Breast Cancer Cells: An In Silico Study - Erwi Putri Setyaningsih; Aditya Helmiansyah; Herdini Herdini; Deyana Citra Insani Sitorus (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Breast cancer is one of the most prevalent malignancies worldwide, with subtypes expressing hormone receptors such as the Estrogen Receptor (ER), Progesterone Receptor (PR), and HER2 being primary therapeutic targets. This study explores the potential of natural compounds as inhibitors for these key proteins. This research aimed to evaluate the potential of bioactive compounds from sappanwood (Biancaea sappan (L.) Tod.), namely Brazilin and its derivative Brazilein, and from the stem of Spatholobus ferrugineus (Zoll. and Moritzi) Benth Variabilin, Medicarpin, and its derivative Vestitol, (-)- as candidate inhibitors against the target proteins of breast cancer (ERα, ERβ, PR, and HER2) using a molecular docking methodology. The analysis was performed by comparing the docking scores and interaction patterns of the test compounds against their native ligands and a reference ligand (lapatinib for HER2). Furthermore, in silico predictions of their pharmacokinetic (ADMET) profiles and drug-likeness were conducted. The docking results showed that Variabilin exhibited the highest binding affinity for HER2 among the test compounds and demonstrated a high predicted binding affinity for the antagonist conformations of both ERα and ERβ. The other test compounds also showed potential as ERα and ERβ inhibitors; however, none of the five compounds showed potential as PR antagonists. The ADMET analysis predicted that the majority of the compounds possess an acceptable pharmacokinetic profile. Variabilin shows favorable docking to the HER2 kinase site and to ER LBDs. Functional activity requires experimental confirmation.